Flight 3U8633 : terrifying experience at 10,000 meters - Zheng, Xiaoming, (SAGE Business. Cases., 2020)
On May 14 2018, 119 passengers and a crew of 9 on Sichuan Airlines Flight 3U8633 found themselves in a life and death crisis. The captain Liu Chuanjian, aged 46, was following a route that he had flew regularly and knew well. The plane had taken off from Chongqing airport, and was scheduled to cross the Mounts of Four Girls (four high peaks), which reach a height of between 5 thousand and 6 thousand meters, then head to Lhasa Airport at an altitude of 3,600 meters above sea level.When the plane was at its cruising altitude of 9,800 meters, a crack appeared in the glass of the right front windshield. The captain had no time to react as the windshield suddenly exploded; the co-pilot was dragged out of the cockpit by the powerful negative pressure and trapped half in and half out of the plane. Liu found himself confronted by a headwind at the speed of 800 kilometers per hour, a freezing temperature of −40°Celsius, and a lack of oxygen as he was not able to don an oxygen mask. The most immediate fear was that the plane was above very high mountains and could not descend. This meant the depressurized cabin would be starved of oxygen and an ordinary passenger or crew member would struggle to remain conscious for more than a minute. Captain Liu had to recover from the shock as quickly as he could, clear his mind of all distractions, and use his willpower and his skills to find a lifeline for himself and the passengers and crew.After a fierce battle that lasted 34 minutes, he succeeded in saving the plane. Following his experience, Liu could see how important it was that qualified pilots should have both expertise in flying techniques and strong mental qualities. In 2019 he took on new responsibilities as a deputy training manager, and was able to reflect on how to instill these qualities in new generations of captains.